A bibliometric review of progress in micro air vehicle research. Issue 2 (June 2017) - Ward, Thomas A; Fearday, Christopher J; Salami, Erfan; Binti Soin, Norhayati
Micro air vehicle research has exponentially expanded since the first articles began to be published in the late 1990s. This article presents a comprehensive bibliometric review of journal articles published on micro air vehicle research from 1998 until 2015. The articles are classified into three types of micro air vehicle: fixed-wing, rotary-wing, and flapping-wing (biomimetic). These types are based upon their primary means of generating lift and propulsive thrust. The specific type of research in these articles is also examined, divided into subcategories of: aerodynamics; guidance, navigation, and control; propulsion; structures and materials; and system design. Numerous bibliometric indicators are presented and analyzed to understand how micro air vehicle research is expanding, which authoring organizations are leading the research, which external sponsoring organizations are providing funding, and the challenges that remain for future researchers. The analysis shows that the majority of the research articles are being written by organizations from the US, China, UK, France, and South Korea. Although biomimetic micro air vehicles are currently the most popular type of micro air vehicle, in recent years the growing popularity of rotary-wing micro air vehicles (especially as a guidance, navigation, and control test platform) has caused it to rival biomimetic micro air vehicles in popularity.